Professores do Atendimento Educacional Especializado em atividade de ensino do conceito de número: uma perspectiva a partir da Teoria da Atividade - Criminazzo, Mariana Aparecida Mesquita (2024)
The aim of this research was to investigate how Specialized Educational Assistance (SEA) teachers organize their teaching so that students appropriate the concept of number. Specifically, based on the answers to a questionnaire and a fictitious case it aimed to develop, apply and evaluate a training proposal for these teachers, based on the assumptions of the Teaching Guiding Activity (TGA), whose elements are referenced in Leontiev's Activity Theory. In this way, we were able to verify, using some categories of Dialectical Historical Materialism and Cultural-Historical Theory, how the theoretical and practical contributions influenced the transformation and appropriation of the teachers' conceptual thinking. The data suggests that the teachers' knowledge was related to the external links of the concept, by proposing activities primarily focused on tracing the numbers and recognizing the graphic symbol associated with the quantities, which also revealed a lack of conceptual knowledge. The analyses showed that this research played its part in contributing to, if not breaking with practices based on the hegemonic knowledge of formal logic, at least raising important questions about the intentional organization of the teaching of the concept of number, because by knowing the logical-historical movement of this concept, it is possible to reveal what formal logic strives to hide. In addition, the data presented in this study shows us the urgent need for this type of knowledge on the part of education professionals, as well as a greater depth in the appropriation of some of the concept's links, such as Grouping, Base of the Decimal Numbering System and Positional Value.